Development of a Respirable Dust Mitigation System for a High Longwall Face at Sihe Colliery in China â a Case Study - Junfeng Wang; Yibo Tang; Hailong Du; Weiwei Shang (Journal of Engineering and Technological Sciences, 2017)
Dust is a major hazard in underground coal mines that threatens the work health and safety of coal miners. The dust issue becomes increasingly significant with the development of highly mechanized coal mining. This issue is particularly serious at the high longwall faces of the Sihe colliery in China as the concentration of dust, in particular respirable dust, at these faces far exceeds the regulatory dust limits. Field testing and computational fluid dynamics (CFD) simulations were conducted to understand the sources of dust generation and its dynamic movement in the #5301 longwall face of high-cutting height at the colliery. The investigation results showed that shearer generated dust was minimal during the coal cutting operation; that face spalling and chock movement were the main dust generating sources, causing significant contamination to the walkway; and that the majority of dust particles from the face (regardless of source) eventually disperse into the main gate, where the dust concentration was greater than 500 mg/m3. These findings were used to develop an effective coal dust mitigation system involving the installation of dust scrubbers, curtains, and venture and crescent sprays. The results of CFD modeling indicate that the dust concentration could be significantly reduced by adopting the new dust mitigation system.